WDR75: An essential protein for ribosome assembly undergoing purifying selection - Lauren Lee; Justen B. Whittall (PLoS ONE, 2025)
Ribosomes, vital for life, consist of a large subunit and a small subunit (SSU), the latter is crucial for translation initiation and mRNA binding. The SSU processome, a 71-protein multimer in humans, is an intermediate in ribosome formation. One of its constituents, WDR75 plays a pivotal role by binding to an evolutionary conserved motif in the external transcribed spacer region of the rRNA to help form the SSU. Herein, we explore mammalian WDR75 molecular evolution, 3D structure, and phylogeny in light of its essential role in the SSU processome. We predict to find the footprint of purifying selection, especially at sites that are essential for proper ribosome assembly. In our comparison of 70 mammalian WDR75 sequences, we found ~25% of sites with significant purifying selection and no evidence of positive selection. Purifying selection was ~5x stronger for sites folding into beta-sheets than those predicted to be coils. Phylogenetic analysis validated expected mammalian relationships and uncovered an unusually long branch leading to mouse-eared bats, exhibiting 18x more substitutions per site than the average mammalian substitution rate. In testing for molecular evolution among branches, we found no evidence for purifying selection along any individual branches, but unexpectedly detected significant diversifying selection solely among African great apes.